2020
DOI: 10.1089/cyber.2019.0271
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Cognitive Stimulation to Improve Cognitive Functioning in Community Elderly: A Controlled Study

Abstract: The advantages of using naturalistic virtual reality (VR) environments based on everyday life tasks for cognitive intervention in the elderly are not yet well understood. The literature suggests that the similarity of such exercises with real life activities may improve generalizability by extending the transfer of gains of training to everyday living. This study aimed to investigate the gains associated with this ecologically-oriented virtual reality cognitive stimulation (VR-CS) versus standard cognitive sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
2
51
0
3
Order By: Relevance
“…87 4.7 | Training and maintenance of cognitive ability 9% (n = 8) of included studies described interventions aiming to improve or preserve cognitive skills and functions and reduce depressive symptoms among older people. [89][90][91][92][93][94][95][96] The interventions used mobile, web-based or virtual reality gaming software, [89][90][91][92]95 wearable and monitoring sensors, 94 a web-based app, 93 and an exercise robot. 96 The system in Lazarou et al 94 also included a caregiver interface for sharing information.…”
Section: Education To Support Self-efficacy and Social Inclusionmentioning
confidence: 99%
“…87 4.7 | Training and maintenance of cognitive ability 9% (n = 8) of included studies described interventions aiming to improve or preserve cognitive skills and functions and reduce depressive symptoms among older people. [89][90][91][92][93][94][95][96] The interventions used mobile, web-based or virtual reality gaming software, [89][90][91][92]95 wearable and monitoring sensors, 94 a web-based app, 93 and an exercise robot. 96 The system in Lazarou et al 94 also included a caregiver interface for sharing information.…”
Section: Education To Support Self-efficacy and Social Inclusionmentioning
confidence: 99%
“…The interaction between the human mind and virtual realities has been demonstrated to improve cognitive functions [17][18][19][20][21][22]. Biologically, this effect cannot be achieved without the activation of some forms of neural plasticity, such as strengthening or attenuation of synaptic transmission [23], remodeling of synaptic connections [24], reshaping of dendritic spines [25][26][27][28], reorganization of neuronal morphology [29][30][31], or modulation of electric excitability [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological test score improvements after traditional pen-and-paper or computerized cognitive training have been found in measures of global composite cognition [40][41][42], verbal memory [11,40,43,44], verbal letter uency [40,41], verbal uency, [45,46], and visuospatial function in the clock-drawing test [40,47]. It has also been reported that VR cognitive training was effective in improving frontal executive function in those with MCI [48], as well as attention and visual memory in older adults [49,50]. In line with these previous studies, our results also showed that multidomain cognitive training in a virtual environment was effective in improving language, visuospatial function, memory (immediate/delayed recall), and frontal executive function compared to pre-training baseline values, but a group difference was found only for visuospatial function.…”
Section: Discussionmentioning
confidence: 95%
“…In recent studies with VR evaluation, investigators were able to effectively differentiate between the navigational [53] and visuospatial de cits seen in MCI patients from healthy older adults [54,55]. In studies with VR intervention, authors have found that VR cognitive training was effective [49,56] or ineffective [50,57] in improving visuospatial function in older adults or those in the early stage of dementia. We believe that the cognitive training performed in the maximally immersive environment with the head-mounted display, headphones, and hand movement trackers in our study might have increased visuospatial functioning in those in the pre-stage of dementia [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation